Risk Aversion and Insurance Propensity - Maccheroni, Fabio; Marinacci, Massimo; Wang, Ruodu; Wu, Qinyu (American Economic Review, 2025)
We provide a new foundation of risk aversion by showing that this attitude is fully captured by the propensity to seize insurance opportunities. In our main results, we first characterize Arrow-Pratt (1963–1964) risk aversion in terms of propensity to full insurance and the stronger notion of risk aversion of Rothschild and Stiglitz (1970) in terms of propensity to partial insurance. We then extend the analysis to comparative risk aversion by showing that the classical notion of Yaari (1969) corresponds to comparative propensity to full insurance, while the stronger notion of Ross (1981) corresponds to comparative propensity to partial insurance. (JEL D81, G22, G52)